Implementasi Metode Complex Proportional Assessment Untuk Pemilihan Reseller Terbaik Pada CV. Harapan Karya Mandiri Bengkulu - Olvi Mariani; Juju Jumadi; Abdussalam Al Akbar (UNIVED Press, 2025)
A reseller is someone who resells products from a supplier to consumers using the reseller's price. The role of resellers cannot be separated from business competition. Resellers are one of the sales methods used by sellers to sell products to customers. For CV. HKM Bengkulu, it is certainly not an easy task to evaluate the performance of resellers achieved by each reseller for the company. Therefore, a computerized decision-making system is needed to assist and simplify the selection of the best reseller. Decision Support System (DSS) research method used in this study is the waterfall method. COPRAS method analysis that will be carried out in this research will describe the stages needed to implement COPRAS in selecting the best reseller at CV. Harapan Karya Mandiri Bengkulu. To perform the calculation process using COPRAS method, the determination of alternatives (An) and criteria, as well as the weights of each criterion, will be conducted. The criteria used are payment type, transaction volume, total spending, quantity of purchases, and subscription duration. The conclusion of this research explains the results of the calculation using COPRAS method, where the reseller with the highest value will occupy the highest ranking followed by the reseller with the lowest value.